ISLAMIC INNER ENERGY THROUGH PAPER STROKES: A FREE EXPRESSION OF SWOT ANALYSIS - Imtihanatul Ma'isyatuts Tsalitsah; Marini; Muhammad Wahid Nur Tualeka; Muhammad Hanifuddin Hakim; Siefanny Puspita Ningrum; Muhammad Nabiel (P3I UMSurabaya, 2025)
This study aims to explore the integration of Islamic values in an art-based psychoeducational intervention as a medium for self-reflection among Muslim students. Using the SWOT analysis framework and the Islamic practice of muhasabah (self-reflection), this research was designed as a workshop focused on enhancing self-awareness, understanding personal potential, and strengthening the spiritual dimension. Participants consisted of 54 fourth-semester students aged 19–21 from the Psychology Study Program at Universitas Muhammadiyah Surabaya. The intervention was implemented in three sessions: (1) psychoeducation on the concept of self-energy and SWOT reflection from an Islamic perspective, (2) self-reflection through free art expression (paper drawing), and (3) reflective discussion and meaning-making. Observational findings showed increased self-awareness, stronger emotional engagement, and active participation throughout the intervention. Non-verbal artistic expression effectively helped participants access emotional layers that are often difficult to express verbally. The integration of Islamic values enriched the reflection process by providing spiritual meaning and moral direction. These findings highlight that value-based and art-based psychoeducational approaches can be effective strategies to support mental health and positive identity development among Muslim students.